Effect of Nutritional Supplementation and Anabolic Androgen with Testosterone on Kidney and Liver Function of Athletes in Baghdad City - Firas Salih Abdulhadi (Journal of Global Pharma Technology, 2018)
This research was conducted to explore the impact of hormones and protein supplementabuseon liver and kidney function and some physiological parameters of athletes. Twenty four volunteers were split equally into two groups, group A: athletes who used androgenic hormones for more than six month, group B: athletes who used proteins and group C: eight volunteers male are normal control without use of any hormones or nutritional supplementation. This research studied intake effect on serum urea, creatinine, total protein, aspartate aminotransferase (AST), alkaline aminotransferase (ALT), sodium, potassium and calcium in the three groups. Results showed a significant elevate (P<0.05) in the level of urea, creatinine, AST and ALT for group A and B compared with the control group, but total protein was lower in group A and control group compared with group B. Furthermore, sodium significantly (P<0.05) decreased in group A and group B compared with control group, on the contrary potassium level and the calcium were significantly decreased in control group compared with group A&B.Keywords: Nutritional supplementation, Anabolic Androgen with testosterone, Kidney, Liver.